ANALYSIS OF AIR-TRAFFIC THREATS - Hana PAČAIOVÁ; Marianna TOMAŠKOVÁ; Michaela BALÁŽIKOVÁ; Jozef KRAJŇÁK (Scientific Journal of Silesian University of Technology. Series Transport)
Globally, air transport has seen a greater increase in recent years. This manuscript is divided into three parts for analysing the negative effects of aviation. The first part is focused on the identification of sources of aircraft noise. While the second part of this article describes the basic principles of the construction and operation of an aircraft jet engine concerning the gaseous emissions produced by such an engine (Third part missing?). The main benefit of this article is the evaluation of the reliability of the human factor because the human factor is an integral part of technical systems and processes. Reliability assessment was performed using the TESEO method. The ergonomic parameter, that is, the cabin noise, was quantified in the given method. The measurement was performed on two types of aircraft, namely in the cabin of a transport jet aircraft and in the cabin of asmall transport aircraft equipped with turboprop engines.